Pathophysiological metabolic changes associated with disease modify the proarrhythmic risk profile of drugs with potential to prolong repolarisation. (27th January 2022) - TeBay, Clifford; McArthur, Jeffrey R.; Mangala, Melissa; Kerr, Nicholas; Heitmann, Stewart; Perry, Matthew D.; Windley, Monique J.; Vandenberg, Jamie I.; Hill, Adam P.
Abstract : Background and Purpose: Hydroxychloroquine, chloroquine and azithromycin are three drugs that were proposed to treat coronavirus disease 2019 (COVID‐19). While concern already existed around their proarrhythmic potential, there are little data regarding how altered physiological states encountered in patients such as febrile state, electrolyte imbalances or acidosis might change their risk profiles. Experimental Approach: Potency of human ether‐à‐go‐go related gene (hERG) block was measured using high‐throughput electrophysiology in the presence of variable environmental factors. These potencies informed simulations to predict population risk profiles. Effects on cardiac repolarisation were verified in human induced pluripotent stem cell‐derived cardiomyocytes from multiple individuals. Key Results: Chloroquine and hydroxychloroquine blocked hERG with IC50 of 1.47 ± 0.07 and 3.78 ± 0.17 μM, respectively, indicating proarrhythmic risk at concentrations effective against severe acute respiratory syndrome‐coronovirus‐2 (SARS‐CoV‐2) in vitro. Hypokalaemia and hypermagnesaemia increased potency of chloroquine and hydroxychloroquine, indicating increased proarrhythmic risk. Acidosis significantly reduced potency of all drugs, whereas increased temperature decreased potency of chloroquine and hydroxychloroquine against hERG but increased potency for azithromycin. In silico simulations demonstrated that proarrhythmic risk was increased by female sex, hypokalaemia and heart failure and identified specific genetic backgrounds associated with emergence of arrhythmia. Conclusion and Implications: Our study demonstrates how proarrhythmic risk can be exacerbated by metabolic changes and pre‐existing disease. More broadly, the study acts as a blueprint for how high‐throughput in vitro screening, combined with in silico simulations, can help guide both preclinical screening and clinical management of patients in relation to drugs with potential to prolong repolarisation.